2002
DOI: 10.1021/pr025517j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Profiling of Proteins in Complex Mixtures Using Liquid Chromatography and Mass Spectrometry

Abstract: The objective of this study was to determine if liquid chromatography mass spectrometry (LC/MS) data of tryptic digests of proteins can be used for quantitation. In theory, the peak area of peptides should correlate to their concentration; hence, the peak areas of peptides from one protein should correlate to the concentration of that particular protein. To evaluate this hypothesis, different amounts of tryptic digests of myoglobin were analyzed by LC/MS in a wide range between 10 fmol and 100 pmol. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
266
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(277 citation statements)
references
References 23 publications
3
266
0
5
Order By: Relevance
“…More recently, this concept has been extended to high-resolution data to include contributions of 13 C isotopes to the overall signal intensities [75]. The intensity value for each peptide in one experiment can then be compared to the respective signals in one or more other experiments to yield relative quantitative information [74,[76][77][78][79][80]. For proteomic analysis of very complex peptide mixtures, three important experimental parameters affect the analytical accuracy of quantification by ion intensities.…”
Section: Label-free Quantificationmentioning
confidence: 99%
“…More recently, this concept has been extended to high-resolution data to include contributions of 13 C isotopes to the overall signal intensities [75]. The intensity value for each peptide in one experiment can then be compared to the respective signals in one or more other experiments to yield relative quantitative information [74,[76][77][78][79][80]. For proteomic analysis of very complex peptide mixtures, three important experimental parameters affect the analytical accuracy of quantification by ion intensities.…”
Section: Label-free Quantificationmentioning
confidence: 99%
“…For this assumption to be valid, the ionization source used to generate metabolite ions should give a linear response to increased metabolite abundance, as has been demonstrated with ESI-MS for low concentrations of simple peptide mixtures [150,151]. Expanding on these demonstrations, Wang et al [152] compared peptide abundance ratios, calculated from direct peak intensities, to expected ratios for three sets of simple protein mixtures; a median coefficient of variability (CV) of 25.7% was reported for 2700 peptides observed across replicates.…”
Section: Label-free Techniquesmentioning
confidence: 99%
“…Briefly, the label-free method specifically finds statistically significant differences in the intensity of both high-abundance and low-abundance ions that account for the variability of measured intensities [39]. Several controlled studies have demonstrated linear responses of peptide ion peaks and showed that mass spectral peak intensities of peptide ions correlate well with protein abundances [41][42][43] and approximately two-fold differences can be detected [39]. In other reports, RSDs of ,11% were obtained [41,42] and more than 50% and nearly 90% of peptide ion ratios showed deviations that were less than 10 and 20%, respectively [44].…”
Section: "Labeled" and "Label-free" Technologiesmentioning
confidence: 99%